2009
DOI: 10.2495/dne-v4-n2-105-122
|View full text |Cite
|
Sign up to set email alerts
|

Understanding design in nature can benefit product conceptual design

Abstract: Product design is a strategic activity in companies due to the intense competition, more sophisticated market needs, and diverse and rapid changes in technology. Effective engineering design can improve quality, reduce costs and lead-time, thereby better satisfying customer needs. The means to reduce cost, time to market and to improve product quality are more complicated. Product performance, quality, aesthetic and reliability, once considered as fundamental factors in developing new products, are now minimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This may increase significantly the productivity of the production of baskets of diverse shape and size, which are traditional Mixtec products. Regarding architectural systems, a system to dampen earthquake vibration has been conceived, as reported elsewhere [15], and a demonstration house will be built over the next 2 years.…”
Section: Development Projectsmentioning
confidence: 99%
“…This may increase significantly the productivity of the production of baskets of diverse shape and size, which are traditional Mixtec products. Regarding architectural systems, a system to dampen earthquake vibration has been conceived, as reported elsewhere [15], and a demonstration house will be built over the next 2 years.…”
Section: Development Projectsmentioning
confidence: 99%
“…Santos-Reyes and Lawlor-Wright propose developing structural models of the manmade systems that need to be improved. Structural models help to understand all the system parts and their relations and pinpoint characteristics that need to be changed by using functionalities from a recognized natural system [8]. Similarly, López Forniés and Berges Muro suggest conducting a functional analysis of a system (product), then doing the biological research, translating the found solutions into key functions, and using them for product concepts [9].…”
Section: Introductionmentioning
confidence: 99%